Performance of Hybrid Strengthening System for Reinforced Concrete Member Using CFRP Composites Inside and over Transverse Groove Technique - Ahmed H. Al-Abdwais; Adil K. Al-Tamimi (Fibers, 2025)
The use of a carbon-fiber-reinforced polymer (CFRP) for structural strengthening has been widely adopted in recent decades. Early studies focused on externally bonded (EB) techniques, but premature delamination of CFRP from concrete surfaces often limited their efficiency. To address this, alternative methods, such as Externally Bonded Reinforcement Over Grooves (EBROG) and Externally Bonded Reinforcement Inside Grooves (EBRIG), were developed to enhance the bond strength and delay delamination. While most research has examined longitudinal groove layouts, this study investigates a hybrid system combining a CFRP fabric bonded inside transverse grooves (EBRITG) with externally bonded layers over the grooves (EBROTG). The system leverages the grooves’ surface area to anchor the CFRP and improve the bonding strength. Seven RC beams were tested in two stages: five beams with varied strengthening methods (EBROG, EBRIG, and hybrid) in the first stage and two beams with a hybrid system and concrete cover anchorage in the second stage. Results demonstrated significant flexural capacity improvement—57% and 72.5% increase with two and three CFRP layers, respectively—compared to the EBROG method, confirming the hybrid system’s superior bonding efficiency.